ҚАЗАҚСТАН НАРЫҒЫНДА БРЕНДИНГТІҢ ДАМУЫ - R. K. Sabirova; A. D. Mukasheva; A. D. Tairova (Экономика: стратегия и практика, 2019)
Branding in the direction of national manufacturers for the Republic of Kazakhstan is a method of implementing many government programs. The role of the brand is becoming more relevant in the market, as the competitiveness of business is growing. The main goal of this article is to give recommendations on theoretical definitions of perfection of marketing technology of brand management, such as globalization of market spheres, wide development of information technologies and competitive struggle in the context of innovative development.Taking into account the fact that the image of Kazakhstan is moving forward, we still see shortcomings. The socio-economic relations between the image of Kazakhstan and marketing technology, aimed at increasing the competitiveness of the national economy in a scientific article, indicate the need for research.The scientific novelty of the research is to analyze and systematize scientific approaches to the development of brand management in the management of brand marketing, which has a competitive advantage, the development of marketing technologies used in brand management.Theoretical research results can be used for theoretical mastering of marketing issues and brand management. The developed methodological recommendations and recommendations on the use of marketing technologies for brand management will increase the consumer value of the corporate brand in the future and will form strategic competitive advantages in the company.At the same time, macroeconomic factors were considered, as well as technological factors affecting branding. In recent years, the information sector has become one of the tools of the modern economy, when society shifted from the forms of industrial development to post-industrial development. The article discusses the development of the brand of telecommunications companies as an emerging general branding.